Recent progress in DNA methyltransferase inhibitors as anticancer agents - Zhang, Zhixiong; Wang, Guan; Li, Yuyan; Lei, Dongsheng; Xiang, Jin; Ouyang, Liang; Wang, Yanyan; Yang, Jinliang (Frontiers in Pharmacology, 2022)
DNA methylation mediated by DNA methyltransferase is an important epigenetic process that regulates gene expression in mammals, which plays a key role in cancer by silencing certain genes, such as tumor suppressor genes, and it has become a promising therapeutic target for cancer treatment. Similar to other epigenetic targets, DNA methyltransferase also can be modulated by chemical agents, and four agents have been already approved to treat hematological cancers. In order to promote the development of DNA methyltransferase inhibitor as anti-tumor agent, in the current review, we discussed the relationship between DNA methylation and tumor, the anti-tumor mechanism, the research progress and pharmacological properties of DNA methyltransferase inhibitor, followed by the possible future research trend of DNA methyltransferase inhibitor.